Warming increases richness and shapes assemblages of eukaryotic parasitic plankton - Amruta Rajarajan; Sławek Cerbin; Kingsly C. Beng; Michael T. Monaghan; Justyna Wolinska (Environmental Microbiome)
Abstract Background Anthropogenic activities have led to a global rise in water temperatures, prompting increased interest in how warming affects infectious disease ecology. While most studies have focused on individual host-parasite systems, there is a gap in understanding the impact of warming on multi-host, multi-parasite assemblages in natural ecosystems. To address this gap, we investigated freshwater eukaryotic parasite communities in ten natural lakes near Konin, Poland: five artificially heated and five non-heated “control” lakes. Since 1958, the heated lakes have experienced a mean annual temperature increase of 2 °C due to hot water discharge from two adjacent power plants. We collected seasonal environmental DNA (eDNA) samples from surface waters over a two-year period and applied targeted metabarcoding to compare the richness and distribution of eukaryotic parasites across lake types with a focus on protists and fungi. Results Using literature searches and sequence metadata from GenBank, we identified putative parasites which included Alveolates, Stramenopiles, basal Fungi and Ichthyosporeans as well as their associated hosts. Heated lakes harboured distinct parasite assemblages with higher richness of chytrids and aphelids, suggesting thermal preferences among certain freshwater microeukaryotic parasites. Other groups exhibited clear seasonal trends with richness of oomycetes peaking in spring and summer, and that of Cryptomycota in winter and autumn. A general linear model revealed a marginally positive correlation between chytrid parasite richness and richness of their green algal, diatom, and dinoflagellate hosts. Post-hoc analyses indicated that heated lakes exhibited greater seasonal variation in chytrid parasite richness and a stronger correlation between host and parasite richness than control lakes. Conclusion These findings demonstrate that warming can induce strong shifts in the richness and assemblages of freshwater microeukaryotic parasites. Using chytrids as a focal group, we additionally demonstrate that warming may amplify seasonal variation in parasite richness and strengthen host-parasite richness relationships.